On Some Diatoms from Upper Mustang Trans-Himalaya Region, Nepal - Subba, B.R.; Pandey, M.R.; Limbu, K.P.; Rai, S.K. (Our Nature, 2010)
This paper deals with the diatoms from Upper Mustang Trans-Himalaya Region, Nepal. Key words: Algae, Diatoms, Upper Mustang Trans-Himalaya, Nepal DOI: 10.3126/on.v7i1.2583 Our Nature (2009) 7:243-247